Efecto de la utilización de Hierbabuena (mentha spicata) y Paico (chenopodium ambrosioides) suministrado a través de bloques nutricionales para el control de parásitos intestinales en Cuyes (cavia porcellus) destetados. - Llerena Caiza, Alvaro Steven (2022)
This research study was carried out in Quero canton, province of Tungurahua with the purpose of evaluating the effect of peppermint, paico, and their combination in nutritional blocks for the control of gastrointestinal parasites in 21-day old-male guinea pigs during 6 weeks. A completely randomized design was used, and the treatments were divided into T0 (control), T1 (peppermint), T2 (paico), and T3 (peppermint and paico) with 8 experimental units each, carrying out 3 assessments to analyze the initial, middle and final parasite load. The coproparasitic test of choice was the Sheather flotation technique. The average parasite load at day 1 per Paraspidodera uncinata treatment was 26 eggs, Eimeria caviae 19 eggs, Capillaria sp. 2 eggs, and Passalurus ambiguus 7 eggs; at the end of the study, there was a statistical decrease in T3 with 1 egg, T2 with 2 eggs, T1 with 5 eggs and T0 with 53 eggs, being Paraspidodera uncinata the only parasite that could not be completely eliminated in the treatments. The bromatological characterization of the plants showed that peppermint has higher protein (20.17%) and fiber (14.23%), while paico has higher fat (2.01%) and dry matter (23.78%). Based on this, the productive parameters showed that a higher final weight was reached in T3 with 641.25 g., weight gain in T3 with 54.88 g., and better feed conversion in T0 with 4.68 g.; achieving a cost-benefit ratio of 1.16 in T0 and 1.15 in the rest of the treatments.